2022
DOI: 10.1002/jsfa.12007
|View full text |Cite
|
Sign up to set email alerts
|

Comparative assessment of antioxidant and immunomodulatory properties of skimmed milk protein hydrolysates and their incorporation in beverage mix

Abstract: BACKGROUND: Milk-derived protein hydrolysates have generated a great deal of interest recently due to their numerous beneficial health effects. However, there are few comparative studies on protein hydrolysates from different dairy species, their production, characterization, and bioactivity. In the present study, skimmed milk from both major and minor dairy species was hydrolyzed with alcalase, and its protein profiles were studied using tricine polyacrylamide gel electrophoresis and reverse phase-high protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 29 publications
0
1
0
Order By: Relevance
“…Additionally, another report showed that soya milk consumption could lead to decreased oxidative damage for DNA bases [ 37 ]. Moreover, skimmed milk proteins exhibited ability of good free-radical quenching [ 38 ]. Antioxidant effect of milk may be protective against cardiovascular disease, while the protective association of semi-skimmed, skimmed, and soy milk with lower risks of all-cause mortality and CVD outcomes needs to be further explored.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, another report showed that soya milk consumption could lead to decreased oxidative damage for DNA bases [ 37 ]. Moreover, skimmed milk proteins exhibited ability of good free-radical quenching [ 38 ]. Antioxidant effect of milk may be protective against cardiovascular disease, while the protective association of semi-skimmed, skimmed, and soy milk with lower risks of all-cause mortality and CVD outcomes needs to be further explored.…”
Section: Discussionmentioning
confidence: 99%
“…In the same study, BM did not seem to reduce the oxidative stress caused by LPS, while in our study, this dairy by-product did protect cells against the oxidative effect of menadione. Furthermore, Prakash et al [37] affirmed that protein hydrolysates from whey and BM contain antioxidant agents and enhancers of phagocytic activity in macrophages. As in our experimental set-up, the dairy fractions were used without hydrolysis, so proteins may not enter the cells.…”
Section: Effect Of Dairy Fractions On Oxidative Stress Caused By Mena...mentioning
confidence: 99%